PRO DAN KONTRA IMPLEMENTASI QANUN SYARIAT ISLAM DI ACEH - Sari, Cut Maya Aprita (Jurnal Review Politik, 2016)
The struggle of Acehnese to get the legality on the implementation of Islamic syar’iah law (also known as qanun) has been conducted since the authority of President Soekarno. The long process of it resulted in the enactment of law No. 11/2006 about The Government of Aceh which confirmed the establishment of Islamic Syar’iah Qanun. However after being established, the qanun experienced a lot of rejection. It is inversely proportional with the condition before the law was established, where Acehnese gave their full support in it. Pro and contra on the implemen- tation of the qanun has continued since 2006. Discriminatory attitudes of the implementer and the incomprehensive of legal content in qanun’s document become a fundamental problem that have to be solved. This paper will discuss about the implementation of Islamic Syar’iah qanun and several factors that led to the emergence of it resistance